Detecção da procedência de plantas psicoativas pelos isótopos estáveis do nitrogênio (15n) e oxigênio (18o) - Melo, Mariane Cristina de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research examines the merits of hallucinogenic plants considered and/or psychoactive substances, such as Cannabis sativa and Ipomoea violacea, using the isotope rates of stable isotope of oxygen (18O) and nitrogen (15N), continuing projects already developed by the research group at the Center for Stable Isotope (CIE), which evaluated the isotopes carbon-13. This paper helps in creating a database that we intent to use in evaluation of each plant merit. Through the IRMS (Isotope-Ratio Mass Spectrometry) technique, it has shown that some of the 24 samples of marijuana (Cannabis sativa L.) evaluated were similar to those grown in the regions of Fairbanks and Tanacross Alaska, USA. In turn, the 50 samples of Ipomoea violacea, coming from Botucatu (SP) and Três Lagoas (MS), got their differences detected, in order to clearly identify the discrepancies between their growing regions. Thus, it was possible not only to track the geographical differences between marijuana samples collected from different regions, but also evaluate the isotopic variation of leaf, flower and seed of Ipomoea violacea. With this database, it was possible to determine the origin region of the drug and/or detect where the cultivation was carried out, aiding in the search of the traffic control agencies, such as the Federal Police in Brazil

Esse trabalho analisa a procedência de plantas consideradas alucinógenas e/ou psicoativas, tais como Cannabis sativa L. e Ipomoea violacea, utilizando a razão isotópica do isótopo estável de oxigênio (18O) e de nitrogênio (15N), dando continuidade a projetos já desenvolvidos pelo grupo de pesquisadores do Centro de Isótopos Estáveis (CIE), os quais avaliaram os isótopos de carbono-13. Esta pesquisa auxilia na criação de um banco de dados, com o qual se pretende avaliar a procedência de cada planta. Através da técnica de IRMS (Isotope-Ratio Mass Spectrometry), demonstrou-se que algumas das 24 amostras de maconha (Cannabis sativa L.) avaliadas apresentaram semelhança com aquelas cultivadas nas regiões de Fairbanks e Tanacross no Alaska, EUA. Por sua vez, as 50 amostras de Ipomoea violacea, oriundas de Botucatu (SP) e Três Lagoas (MS), obtiveram suas diferenças detectadas, de maneira a identificar com clareza as discrepâncias entre suas regiões de cultivo. Assim, foi possível não só detectar diferenças geográficas entre as amostras de maconha, como também avaliar a variação isotópica da folha, flor e semente da Ipomoea violacea. Com esse banco de dados, foi possível determinar a origem da droga e/ou a detecção do local em que foi realizado o cultivo, auxiliando na busca dos órgãos de controle do tráfico, como a Polícia Federal no Brasil
Keywords: Plantas alucinógenas - Identificação; Nitrogenio - Isotopos; Oxigenio - Isotopos; Ensaios de procedencia; Hallucinogenic plants - Identification